Tow New Species of Ceratopogonidae (Diptera) - Franklin B. Lewis (Psyche: A Journal of Entomology)
During an investigation of the bionomics and immature stages of the Ceratopogonidae, two new species were encountered. The purpose of this paper is to describe these insects.